Future fuels for environmental sustainability: Roles of computing - Kasim H.; Omar R.; Bin Muhmat Hilme M.H.; Al-Ghaili A.M. (Mattingley Publishing, 2023)
Carbon footprint; Climate change; Combustion; Environmental technology; Greenhouse gases; Industrial emissions; Intelligent systems; Internet of things; Pollution; Sustainable development; Transportation; Environmental sustainability; Fossil fuel combustion; Information and Communication Technologies; Intelligent transportation systems; Internet communication; Internet of Things (IOT); Renewable energies; Transportation system; Fossil fuels